Exploring the source of well-being for high achiever students - Lalu Hamdian Affandi; H. Husniati; Heri Hadi Saputra (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2021)
Characteristics of high achiever students are different from middle and low achiever students. Teachers and schools need to understand the unique characteristics of high achiever students in terms of their wellbeing. Aim of this research is to describe source of wellbeing for high achiever students. The research was conducted through survey using questionnaire adapted from Huebner’s Multidimensional Student’s Life Satisfaction Scale (MSLSS). The questionnaire filled by 428 students in grade IV-VI in Mataram, West Nusa Tenggara, which are at top ten rank of their class. Data then analyzed by performing exploratory factor analysis. This research found that there are two factors as source of wellbeing for high achiever students, that are physical and psychological safety and the availability of support for student personal growth. Physical and psychological safety refers to school environment that protects students from psychological and physical threats. Whereas the availability of support for personal growth refers to how schools provide environment in order to facilitate students’ cognitive and social development. This research suggest that high achiever students call for teachers and school personnel to create school environment by considering students opportunities to develop their potentials without feeling threatened.